Adubação organomineral e biofertilização líquida na produção de frutos de pinheira ( Annona squamosa L.) no submédio São Francisco, Brasil - Araujo, Jairton Fraga; Leonel, Sarita [UNESP]; Neto, Joaquim Pereira (Universidade Federal de Uberlândia (UFU), 2008)
The organic production systems based on natural processes do not allow the use of synthetic fertilizers with a high solubility, so it is required the use of technologies in accordance with the organic production legislation in order to make the technical, economical and environmental sustainable activities viable. To evaluate the effects of the usage of mineral and organic natural fertilizers, associated with liquid biofertilizers (BLE= enriched liquid biofertilizer and BF= leaf biofertilizers) on the production of the sugar apple fruit crop Annona squamosa L., replacing totally the chemical fertilizers, used by conventional farming systems, a nine year old orchard was driven in the irrigated plot n degrees 1295, irrigated project Nilo Coelho, district of Petrolina - PE. The experiment was carried out from September 2005 to February 2006. The experimental design was done through randomized blocks with eight treatments and four replications in plots of three plants each, with 96 plants in total. The treatments were the following: T(1) - plants with no fertilizer; T(2) - 60 g de N + 32 g de P(2)O(5) + 48 g de K(2)O; T(3) - 90g de N + 32 g de P(2)O(5) + 48 g de K(2)O; T(4) - 30 g de N + 32 g de P(2)O(5) + 48 g de K(2)O + 15 L de BLE + BF a 5 %; T(5) - 60g de N + 32 g de P(2)O(5) + 48 g de K(2)O + 30 L de BLE + BF a 5 %; T(6)- 90g de N + 32 g de P(2)O(5) + 48 g de K(2)O + 45 L de BLE + BF a 5 %; T(7) - 120g de N + 32 g de P(2)O(5) + 48 g de K(2)O + 60 L de BLE + BF a 5 %; T(8) - 150 g de N + 32 g de P(2)O(5) + 48 g de K(2)O + 75 L de BLE + BF a 5 % The fruit growth analyses (diameter and average length), total yield, productivity, average fruit weight, average number of fruits, fresh weight of the skin and pulp and dry weight of the fruits were used to evaluate the experiment. The results were relevant to the total production, fresh weight of the skin and dry weight of the fruits. The use of organominerals associated with liquid fertilizers increased significantly the productivity in values ranging from 10.44% (T(5) = 1.98 t ha(-1)) to 24.52 % (T(7) = 12.34 %). The treatment T(3) stood out (90g de N + 32g de P(2)O(5) + 48g de K(2)O) with a higher production than the control. The fruit weight increased in the fertilized treatments, with values increasing from treatment (T(2) = 5.26 %) to the treatment (T(7) = 12.34 %) in relation to the control. The fruit development was characterized by an average growth increase of 82 % in length and 84 % in diameter until the 56(th) day, with a sigmoidal growth pattern.

Com o objetivo de avaliar o efeito de biofertilizantes líquidos aplicados via solo e via foliar, em associação com adubação orgânica e mineral, na produção e qualidade de frutos da pinheira, conduziu-se experimento com oito tratamentos e quatro repetições em blocos ao acaso, em Petrolina/PE. Os resultados revelaram que os tratamentos T3 ( 90g de N + 32g de P2O5 + 48g de K2O); T4 ( 30g de N + 32g de P2O5 + 48g de K2O + 15 L de BLE + BF a 5%) e T6 (90g de N + 32g de P2O5¬ + 48g de K2O + 45 L de BLE + BF a 5%) foram significativamente superiores aos demais proporcionando aumentos em produtividade. As características número médio de frutos e peso médio de frutos não apresentaram diferenças significativas. Contudo para esta última característica, os pesos médios dos frutos de todos os tratamentos foram superiores em termos absolutos à testemunha.
Organomineral and liquid biofertilization in sugar apple fruit yield (Annona squamosa L.) in the sub-medio Sao Francisco, Brazil
Keywords: Organomineral fertilizing; Liquid biofertilizers; Sugar apple; Growth